ANALISIS KESIAPAN PEMERINTAH DESA DALAM PENGELOLAAN DANA DESA (STUDI KASUS PADA PEMERINTAH DESA PELAWAD KECAMATAN CIRUAS KABUPATEN SERANG) - Usman, Fadlil; Haryanto, Sulistyo Dwi (Polytechnic of State Finance STAN, 2015)
Villagefund isanew source of incomeforthe village government, sourcedfrom the state budget allocation. This fund began to be allocated and disbursed the first time in 2015. The village government will earn huge amounts of money in running the village administration, but on the other hand demanded readiness in the management of village finances better. This study aims to determine the readiness of the Pelawad village government in the management of the Village Fund andknowing the constraintsfaced. The analytical method used is descriptive analysis and index analysis to quantify the level of readiness in managing the Village Fund. Some Factors that support the readiness of the ofthe Village Government in managing the Village Funds are organizational commitment, human resources and information systems. The results showed that Pelawad Village Government has a strong commitment in the management ofthe VillageFund.The quantityof human resourcesare sufficient, whileintermsof quality is not sufficient. The information systems to support the processing of village financial data have been available, but the human resourcesare not fully ready to operate the systems. Pelawad village government readiness in the overall managementof village funds are categorized on the level set by the value of theindex 66.